228k views
4 votes
Solve: -(6x+ 8) = 4(17 - x) *

2 Answers

2 votes

Answer:

−38

Step 1: Simplify both sides of the equation.

−(6x+8)=4(17−x)

−6x+−8=(4)(17)+(4)(−x)(Distribute)

−6x+−8=68+−4x

−6x−8=−4x+68

Step 2: Add 4x to both sides.

−6x−8+4x=−4x+68+4x

−2x−8=68

Step 3: Add 8 to both sides.

−2x−8+8=68+8

−2x=76

Step 4: Divide both sides by -2.

−2x−2=76−2

x=−38

User Carst
by
5.6k points
6 votes

Answer:

Isolate the variable by dividing each side by factors that don't contain the variable.

x = − 38

Explanation:

User WilliamLou
by
4.2k points